MicroRNA166 Modulates Cadmium Tolerance and Accumulation in Rice. Issue 4 (20th June 2018) - Ding, Yanfei; Gong, Shaohua; Wang, Yi; Wang, Feijuan; Bao, Hexigeduleng; Sun, Junwei; Cai, Chong; Yi, Keke; Chen, Zhixiang; Zhu, Cheng
Abstract : miR166-overexpressing plants show lower Cd-induced oxidative stress and Cd accumulation than in wild-type plants. Abstract: MicroRNAs (miRNAs) are 20- to 24-nucleotide small noncoding RNAs that regulate gene expression in eukaryotic organisms. Several plant miRNAs, such as miR166, have vital roles in plant growth, development and responses to environmental stresses. One such environmental stress encountered by crop plants is exposure to cadmium (Cd), an element highly toxic to most organisms, including humans and plants. In this study, we analyzed the role of miR166 in Cd accumulation and tolerance in rice ( Oryza sativa ). The expression levels of miR166 in both root and leaf tissues were significantly higher in the reproductive stage than in the seedling stage in rice. The expression of miR166 in the roots of rice seedlings was reduced after Cd treatment. Overexpression of miR166 in rice improved Cd tolerance, a result associated with the reduction of Cd-induced oxidative stress in transgenic rice plants. Furthermore, overexpression of miR166 reduced both Cd translocation from roots to shoots and Cd accumulation in the grains. miR166 targets genes encoding the class-III homeodomain-Leu zipper (HD-Zip) family proteins in plants. In rice, HOMEODOMAIN CONTAINING PROTEIN4 ( OsHB4 ) gene (Os03g43930), which encodes an HD-Zip protein, was up-regulated by Cd treatment but down-regulated by overexpression of miR166 in transgenic rice plants. Overexpression of OsHB4 increased Cd sensitivity and Cd accumulation in the leaves and grains of transgenic rice plants. By contrast, silencing OsHB4 by RNA interference enhanced Cd tolerance in transgenic rice plants. These results indicate a critical role for miR166 in Cd accumulation and tolerance through regulation of its target gene, OsHB4, in rice.